2020
DOI: 10.1016/j.envpol.2020.114769
|View full text |Cite
|
Sign up to set email alerts
|

Iron solubility in fine particles associated with secondary acidic aerosols in east China

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…PM 2.5 samples were analyzed to obtain water‐soluble ions (i.e., SO42, NO3, NH4+, Ca 2+ , Mg 2+ , K + , Na + , Cl − , and F − ) by an ion chromatography system (Dionex ICs‐90, USA), organic carbon (OC) and elemental carbon (EC) by an OC‐EC analyzer (Sunset Laboratory Inc., USA), and trace metals (i.e., V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Mo, Tc, Rh, Cd, Ag, In, Sn, Sb, Ba, Tb, Lu, Tl, Pb, Bi, Th, and U) by inductively coupled plasma mass spectrometry (ICP‐MS, Agilent 7500ce). The detailed experimental processes were provided in the previous studies (Y. Pan et al., 2013; Zhang, Liu, Wang, et al., 2017; Zhu et al., 2020). Concentrations of organic matter (OM) were obtained by multiplying OC by a factor of 1.91, as reported by Xing et al.…”
Section: Observations and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 samples were analyzed to obtain water‐soluble ions (i.e., SO42, NO3, NH4+, Ca 2+ , Mg 2+ , K + , Na + , Cl − , and F − ) by an ion chromatography system (Dionex ICs‐90, USA), organic carbon (OC) and elemental carbon (EC) by an OC‐EC analyzer (Sunset Laboratory Inc., USA), and trace metals (i.e., V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Mo, Tc, Rh, Cd, Ag, In, Sn, Sb, Ba, Tb, Lu, Tl, Pb, Bi, Th, and U) by inductively coupled plasma mass spectrometry (ICP‐MS, Agilent 7500ce). The detailed experimental processes were provided in the previous studies (Y. Pan et al., 2013; Zhang, Liu, Wang, et al., 2017; Zhu et al., 2020). Concentrations of organic matter (OM) were obtained by multiplying OC by a factor of 1.91, as reported by Xing et al.…”
Section: Observations and Methodsmentioning
confidence: 99%
“…The detailed experimental processes were provided in the previous studies (Y. Pan et al, 2013;Zhang, Liu, Wang, et al, 2017;Zhu et al, 2020). Concentrations of organic matter (OM) were obtained by multiplying OC by a factor of 1.91, as reported by Xing et al (2013).…”
Section: Pm 25 Chemical Composition Analysesmentioning
confidence: 99%
“…The importance of RH in aerosol Fe solubility was also suggested by a few previous studies. For example, Zhu et al (2020) collected aerosol particles during winter at four cities in eastern China, and found that Fe solubility was low (0.7%-3.8%) at <50% RH even though some samples had high values of (2 × [SO 4 (Zhu et al, 2020) and significantly higher (1.3%-11.4%) at >50% RH. In another study, Shi et al (2020) found that for similar (2 × [SO 4…”
Section: Effect Of Acid Processing On Fe Solubilitymentioning
confidence: 99%
“…To further understand abundance and fractional solubility of aerosol Fe in this region, a field campaign was conducted in November-December 2019 at a suburban site in Qingdao, a coastal city in northern China. Compared to previous studies carried out over and around Northwest Pacific (Chuang et al, 2005;Fu, Shang, et al, 2014;Hsu et al, 2005Hsu et al, , 2010Liu et al, 2021;Ooki et al, 2009;Shi et al, 2020;Takahashi et al, 2013;Zhang et al, 2013;Zhu et al, 2020), our work aimed to provide further insights in the following three aspects: (a) fine (<1 μm) and coarse (>1 μm) particles were simultaneously collected. Fine and coarse particles exhibit large difference in sources and compositions (Seinfeld & Pandis, 2016), and therefore Fe solubility and its controlling factors may differ significantly between coarse and fine particles; (b) a number of elements and soluble ions, in addition to total and soluble Fe, were also measured, providing constrains to understand factors which determined aerosol Fe solubility; (c) three representative weather conditions, including clean, haze and dust days, were encountered during the campaign, giving the opportunities to explore and understand aerosol Fe solubility under distinctively different conditions.…”
mentioning
confidence: 99%
“…Both the soluble Fe concentration and soluble Fe fraction showed a positive correlation with PM 2.5 concentration in East China in a previous study (Zhu et al, 2020). The soluble fraction of Fe in aerosols (PM 2.5 ) was observed to be 3%-5% in four urban sites in East China in December 2017 (Zhu et al, 2020). The fraction of Fe 3+ in soluble Fe (Fe 3+ / (Fe 3+ + Fe 2+ )) for aerosols collected in the continental outflow of East China was observed to be about 67% (Moffet et al, 2012).…”
Section: Iron(iii)-induced Photolytic CL 2 Formation Mechanismmentioning
confidence: 54%